2016
DOI: 10.17135/jdhs.2016.16.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association between Average Volume of Alcohol Consumption, Binge Drinking, and Periodontitis among Korean Adults: The Korea National Health and Nutrition Examination Survey, 2013~2014

Abstract: We investigated the gender-specific association between average volume of alcohol consumption, binge drinking, and periodontitis using representative nationwide data. In total, we included 3,549 men and 4,810 women, aged 19 years and older, who participated in the sixth Korea National Health and Nutrition Examination Survey performed in 2013∼2014. According to the average volume of alcohol consumption, study participants were grouped as follows: mild drinkers (0.1∼2.0 drinks/day in men and 0.1∼1.0 drink/day in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hyeong and Lee’s study using the 2013–2014 KNHANES showed that higher alcohol consumption and frequency of binge drinking was linked to higher periodontitis. 36 Kim et al also found that periodontal status was significantly associated with harmful alcohol use. 37 Therefore, dental check-up care needs to be included when nursing officers conduct alcohol-related health interventions for military personnel.…”
Section: Discussionmentioning
confidence: 97%
“…Hyeong and Lee’s study using the 2013–2014 KNHANES showed that higher alcohol consumption and frequency of binge drinking was linked to higher periodontitis. 36 Kim et al also found that periodontal status was significantly associated with harmful alcohol use. 37 Therefore, dental check-up care needs to be included when nursing officers conduct alcohol-related health interventions for military personnel.…”
Section: Discussionmentioning
confidence: 97%
“…Mendelian randomization, an approach to make a casual inference, has been applied to determine the role of alcohol consumption in the development of periodontitis and the result supports that alcohol ingestion is a predisposing factor for periodontitis [ 291 ]. In addition, the correlation between alcohol intake and periodontitis was reported to be gender-specific by some studies, which suggests more significant relevance in male than in female populations [ 292 ]. Corroborating with clinical findings, light alcohol intake does not aggravate ligature-induced damage of alveolar bone and even seems to protect against bone loss at unligated sites in rats [ 293 ].…”
Section: Lifestylementioning
confidence: 99%